2014
DOI: 10.1111/poms.12107
|View full text |Cite
|
Sign up to set email alerts
|

Improving Humanitarian Operations through Technology‐Enabled Collaboration

Abstract: Humanitarian supply chains involve many different entities, such as government, military, private, and non‐governmental organizations and individuals. Well‐coordinated interactions between entities can lead to synergies and improved humanitarian outcomes. Information technology (IT) tools can help facilitate collaboration, but cost and other barriers have limited their use. We document the use of an IT tool to improve last‐mile supply distribution and data management in one of many camps for internally displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 32 publications
1
108
0
12
Order By: Relevance
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
“…These tools provide many benefits such as increased data accuracy and operational efficiency and, perhaps more importantly for aid organizations, enhanced transparency of in-kind donations and supplies at various junctions in the supply chain. In fact, using technology is an increasingly pervasive approach to supplement and invigorate aid efforts in developing nations (Ergun et al, 2014). Despite this context's potential to inform the broader debate on technology's role in society at large and to highlight technology's potential to create direct and lasting good, few empirical studies in the operations research and related literatures evaluate the efficacy of relevant technology solutions.…”
Section: Hom and It's Supporting Rolementioning
confidence: 99%
“…Thomas and Kopczak (2005) identify a lack of IT resources as one of five critical barriers to effective humanitarian logistics. The issue is compounded by the high costs of many IT solutions, which preclude their use in many humanitarian operations (Ergun et al 2014). Additionally, many donors prefer their money to be used for immediate, tangible relief supplies instead of for management infrastructure, such as information systems or logistical equipment (Oloruntoba and Gray 2006).…”
Section: Key Characteristics Of Humanitarian Logisticsmentioning
confidence: 99%
“…The benefits of route optimization translate to both relief efforts, focusing on delivery speed, and development efforts, in which cost and efficiency become more important considerations (Pedraza-Martinez et al 2011). In relief situations, Ergun et al (2014) found that desktop and laptop computers are the most common systems (after paper systems) employed by relief organizations in Haiti. We suspect that this state of affairs also holds elsewhere; such relief organization have available at least basic computer technology, making our solution feasible for use in many disaster relief situations.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%